Effect of short-term exercise training on brain-derived neurotrophic factor signaling in spontaneously hypertensive rats. Issue 2 (February 2017) - Monnier, Alice; Garnier, Philippe; Quirie, Aurore; Pernet, Nicolas; Demougeot, Céline; Marie, Christine; Prigent-Tessier, Anne
Abstract : Objective: Decreased brain-derived neurotrophic factor (BDNF) level has been reported in the hippocampus of hypertensive rats. The present study explored whether brain neurons and/or endothelial cells are targeted by hypertension with respect to BDNF expression and the potential of physical exercise to cope with hypertension. Methods: Physical exercise was induced in spontaneously hypertensive rats (SHR) and Wistar Kyoto (WKY) rats. The hippocampus of sedentary and exercised rats ( n  = 6 for each group) were used for western blots to assess proBDNF, mature BDNF (mBDNF), tropomyosin-related kinase B (TrkB), P-TrkB tyr816 (TrkB phosphorylated at tyrosine 816), synaptophysin, endothelial nitric oxide synthase (eNOS) and eNOS phosphorylated at serine 1177 protein levels. BDNF and proBDNF localization in the hippocampus was studied in WKY rats, SHR and exercised SHR ( n  = 5 each). mBDNF and proBDNF protein levels were also assessed in hippocampal slices prepared from SHR ( n  = 10) that were incubated for 24 h with the nitric oxide (NO) donor glyceryl trinitrate. SBP was measured by the tail-cuff method. Results: Exercise modified blood pressure neither in SHR nor WKY. As compared with WKY rats, SHR displayed decreased levels of mBDNF, P-TrkB tyr816, synaptophysin, eNOS and eNOS phosphorylated at serine 1177 but no change in proBDNF and TrkB levels. These effects coincided with low BDNF staining in both endothelial cells and neurons. Exercise improved the endothelium-derived NO system and the BDNF pathway in both strains. The NO donor increased mBDNF but decreased proBDNF levels. Conclusion: Our results revealed that endothelial and neuronal BDNF expressions were both impaired in hypertension and that physical exercise improved hippocampal mBDNF levels and signaling through blood pressure–independent mechanisms.